The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nu12113312
|View full text |Cite
|
Sign up to set email alerts
|

How Is Functional Food Advertising Understood? An Approximation in University Students

Abstract: In functional food advertising, messages are not always easily understandable for the target audience. Current European legislation, enforced through Regulation 1924/2006, specifies that such messages should be clear and precise so as not to mislead the consumer. The objective of this study was to observe consumers’ understanding of messages in functional food advertisements. The methodology used was a self-administered survey filled out by 191 students enrolled in a Degree in Advertising and Public Relations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…Communications and marketing professionals in the industry should carefully consider how to design labels, position brands, and develop advertising campaigns. According to results from the reviewed studies, functional food product labels should accurately and precisely communicate information about the type of functional ingredient and its benefits to human health [32,70,71,73]. Providing this type of health information on labels can significantly increase consumers' acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communications and marketing professionals in the industry should carefully consider how to design labels, position brands, and develop advertising campaigns. According to results from the reviewed studies, functional food product labels should accurately and precisely communicate information about the type of functional ingredient and its benefits to human health [32,70,71,73]. Providing this type of health information on labels can significantly increase consumers' acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, certain health information on food labels may improve consumers' perceptions of health benefits and positively influence their acceptance [70]. Specifically, González-Díaz et al [71] found that health information, such as the type of added functional ingredients and how they benefit human health, may lead to higher purchase intentions. Ahn et al [72] explained that less informed consumers who did not fully understand the health attributes of functional products were unwilling to consume functional foods.…”
Section: Health Informationmentioning
confidence: 99%
“…Today, next to a distinctive taste and standard nutritional values, foodstuffs are expected to provide additional health benefits. This is what functional food can do, especially if enriched with biologically active secondary plant metabolites, such as polyphenols [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Communications and marketing professionals in the industry should carefully consider how to design labels, position brands, and develop advertisings. According to results from the reviewed studies, functional food product labels should accurately and precisely communicate information about the type of functional ingredient and its benefits to human health [32,70,71,73]. Providing this type of health information on labels can significantly increase consumers' acceptance.…”
Section: Discussionmentioning
confidence: 99%